Evaluating the dynamic sustainability and resilience of a hybrid urban system: case of Chengdu, China. (1st April 2021) - Mou, Yu; Luo, Yuyan; Su, Zerui; Wang, Jun; Liu, Tao
Abstract: Cities are faced with booming populations, limited resources, and intensified pollution. To remain its sustainability and resilience against the varying environment, a city has to tackle the challenges from both the nature and human ourselves. This paper aims at evaluating the sustainability and resilience of cities in terms of their capabilities for maintaining, in face of potential threats in the future. Five subsystems, i.e. economy, environment, population, resource, science & technology are incorporated in the conceptual framework of linked urban sustainability and resilience. Through scenario simulations, we measure the performance of system elements and evaluate the resilience process with water resources trial when disturbance occurs. With Chengdu, China as the case, we have found that: (1) Limited water resources could not meet the basic demand well, and the quality could not be significantly improved till 2035 under the current path, and the modifications could be done with ongoing strategies. (2) Impacts of disturbances could be largely expanded in resource-dependent period, for which improving resource use efficiency and conducting industry structural adjustment could make cities more resilient. (3) The greater the presence of resilience system elements, the more developed the sustainability system. Highlights: A dynamic hybrid framework system of urban sustainability and resilience is constructed. The performance of sustainability system elements is measured through scenario simulations. Disturbance is introduced in for evaluating urban resilience. The greater the presence of resilience system elements, the more developed the sustainability system.